2019
DOI: 10.28945/4450
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family on Doctoral Student Success

Abstract: Aim/Purpose: This qualitative case-study explores how a doctoral student’s family influences the doctoral student’s success from the perspective of doctoral students who were enrolled in an online doctoral program. Background: Previous research has shown that family can significantly influence doctoral student success; however, it is not clear what is meant by family nor what the details of the influence of family look like from the perspective of the doctoral student. Methodology: A qualitative case-study m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The impact of caregiving responsibilities on work and everyday stressors related to family, lifestyle, and employment was identified as significant predictors. Some studies reported that doctoral students would frequently feel burned out between household and employment responsibilities (Breitenbach et al, 2019 ; Woolston, 2019 ). As a result, graduate students would often indulge themselves in physical activities, such as exercise and cycling, or stress-relieving activities, such as yoga (Kumar & Cavallaro, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of caregiving responsibilities on work and everyday stressors related to family, lifestyle, and employment was identified as significant predictors. Some studies reported that doctoral students would frequently feel burned out between household and employment responsibilities (Breitenbach et al, 2019 ; Woolston, 2019 ). As a result, graduate students would often indulge themselves in physical activities, such as exercise and cycling, or stress-relieving activities, such as yoga (Kumar & Cavallaro, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a grounded theory study examining persistence in online EdD candidates who grew up in poverty, Rockinson-Szapkiw, Spaulding, Swezey, and Wicks (2014) posited that students' persistence is partially attributable to "the degree to which the candidate's sense of connectedness with family members is met while pursuing the doctorate" that "not only includes the maintaining of familial relationships and relatedness (a sense of belonging and care) but also includes the 'fit' between the degree and family values" (Rockinson-Szapkiw, Spaulding, Swezey, & Wicks, 2014, p. 196). Breitenbach, Bernstein, Ayars, and Konecny (2019) similarly found that when distance doctoral students' families valued the degree, the doctoral student felt supported. Conversely, when doctoral students' families did not value the degree or think the pursuit of the degree was a responsible use of money, the student and family experienced stress.…”
Section: The Role Of Family In Doctoral Educationmentioning
confidence: 92%
“…Whereas the financial situation of PhD students working at the university is perceived as unsatisfying, external PhD students often do not have a problem with their financial situation and future prospective as they are supported by a company and will go back to their company after finishing their doctoral degree. Including different types of PhDs and rewards, we gained a broad picture of the perceived rewards that could influence work stress of PhD students instead of looking at single aspects, such as the reward from family members (Breitenbach et al, 2019) or supervisors (Ives & Rowley, 2005).…”
Section: Comparison Of Findings To Literaturementioning
confidence: 99%